2013
DOI: 10.4254/wjh.v5.i9.470
|View full text |Cite
|
Sign up to set email alerts
|

Current role of fenofibrate in the prevention and management of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common health problem with a high mortality burden due to its liver-and vascular-specific complications. It is associated with obesity, high-fat diet as well as with type 2 diabetes mellitus (T2DM) and metabolic syndrome (MetS). Impaired hepatic fatty acid (FA) turnover together with insulin resistance are key players in NAFLD pathogenesis. Peroxisome proliferator-activated receptors (PPARs) are involved in lipid and glucose metabolic pathways. The novel concept i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(55 citation statements)
references
References 109 publications
(185 reference statements)
2
45
0
7
Order By: Relevance
“…Taken together, these results suggest that PPARα or fatty acid oxidation disorders may also participate in the development of human NAFLD. In addition, some studies have demonstrated that PPARα agonist improved liver steatosis in several obese mice models (57)(58)(59). However, the effect of PPARα agonists on improving human NAFLD is still controversial, although some studies have shown positive effects (60,61).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these results suggest that PPARα or fatty acid oxidation disorders may also participate in the development of human NAFLD. In addition, some studies have demonstrated that PPARα agonist improved liver steatosis in several obese mice models (57)(58)(59). However, the effect of PPARα agonists on improving human NAFLD is still controversial, although some studies have shown positive effects (60,61).…”
Section: Methodsmentioning
confidence: 99%
“…It seems that insulin-sensitizing action of fenofibrate is more important to counter hepatic steatosis than its lipid-lowering property. A recent study showed a significant decrease in hepatic transaminases coupled with a marked decrease of hepatocellular ballooning in humans [54,55] . As far as mice models of NASH are concerned, APOE2 mice fed a western diet showed decreased hepatic macrophage accumulation, which precedes lipid accumulation within hepatocyte, and expressive reduction of lipotoxicity after treatment with fenofibrate.…”
Section: Targeting Ppars To Treat Nafldmentioning
confidence: 99%
“…Fenofibrate was found to deplete hepatic triglycerides accumulation in high fat diet [131], reversed the development of hepatic steatosis, necroinflammation and collagen deposition [132]. The drug activated PPAR-α which enhanced hepatic fatty acid turnover, fatty acid transport protein, fatty acid binding protein, carnitine palmitoyltransferase II, as well as medium-and long-chain acyl-CoA dehydrogenase and acyl-CoA oxidase [133].…”
Section: Fenofibratementioning
confidence: 99%